2014
DOI: 10.1007/s00221-014-4135-2
|View full text |Cite
|
Sign up to set email alerts
|

Synchronised and complementary coordination mechanisms in an asymmetric joint aiming task

Abstract: Many forms of social interaction require that behaviour be coordinated in the here and now. Much research has been conducted on how people coordinate their actions in real time to achieve a joint goal, showing that people use both synchronised (i.e., symmetric) and complementary (i.e., asymmetric) strategies. These two mechanisms have been mostly studied independently, the former in the context of rhythmic tasks, and the latter in non-rhythmic tasks. However, people often balance these two strategies in real-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…synchronisation indices, windowed cross-correlations, asynchronies), by ensuring that taps were aligned between pairs54. Thus, if one pair member skipped a beat, the tap of the other was removed, to ensure the shifts in the lagged cross-correlations were not artefactual.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…synchronisation indices, windowed cross-correlations, asynchronies), by ensuring that taps were aligned between pairs54. Thus, if one pair member skipped a beat, the tap of the other was removed, to ensure the shifts in the lagged cross-correlations were not artefactual.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a positive lag +1 correlation would indicate the other member is adapting (and thus is the follower). A positive lag 0 correlation would mean that the participants are correlated in real time, indicating that when one speeds up, the other speeds up as well; finally, a negative lag 0 correlation would mean that the two participants were anti-correlated, such that when one speeds up, the other slows down5458. The coefficients were compared across groups using 2 (OT vs Placebo) × 4 (hearing self; member 1 acting as leader, member 2 acting as follower; member 1 acting as follower, member 2 acting as leader; bidirectional coupling) multivariate analysis of variance (MANOVA) and lag −1, 0, and +1 correlation coefficients as the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…In this perspective, the asymmetric allocation of information between two partners (e.g. leader-follower) is known to shape the kinematics of their movements [14,[17][18][19][20][21]. Role assignment gives the agents the possibility to support coordination by implementing so-called signalling strategies [22,23], for example by systematically making the trajectory of their movements less variable and hence more predictable [14,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Reed et al (2006) have also found an interpersonal complementary relationship in a joint target-acquisition task [also see Skewes et al (2015)]. They asked pairs of participants to move a mark on a disk into a target as quickly as possible and hold it there.…”
Section: Complementary Force Production Is Stronger and Synchronizatmentioning
confidence: 99%
“…Coordination that may occur intentionally between individuals with a common goal in a motor task has recently been studied using the term "joint action" [defined by Ganesh et al (2014); Masumoto and Inui (2014b); Newman-Norlund et al (2008); Sebanz et al (2006); and Skewes et al (2015)]. For example, Bosga and Meulenbroek (2007) asked pairs of participants to perform a virtual lifting task using constant uni-or bimanual isometric force, although they did not examine the hierarchical relation between bimanual and joint actions.…”
mentioning
confidence: 99%